Approach Constructivism To Motivation Studying History of XI IPS Students at SMAN 2 Medan - Anataya, Syaira; Sumantri, Pulung; Aisyah, Sitti (CV. Rayyan Dwi Bharata, 2024)
Study This aim For know influence approach constructivism if implemented fully in the first class No apply similar approach, approach This linked with exists development motivation Study participant educate in eye lesson history in class XI SMAN 2 Medan. Background study This is exists hindering problems ongoing learning process teach in class, anyway problem That is participant educate No own high passion For finish assigned tasks, several among them behave No Spirit when learning ongoing, no there is curiosity to eye lesson to be studied, participants educate new Want to do matter if ordered or not own Good initiative, participant educate too depend to the teacher, no concentrate moment carry out learning, and having little enthusiasm in face challenge. Problem the refer to problem lack motivation Study student see indicators displayed by participants educate. Based on background behind problem that so researcher endeavor give possible approach facilitate development student Good in a way cognitive, affective and psychomotor that is use approach constructivism. Study This use approach quantitative with type study that is Classroom Action Research consisting of of two cycles, where cycle second done For finish cycle problems first one yet resolved or Not yet missed. Population in study This is all over class XI IPS SMAN 2 Medan year teachings 2024/2025 consisting of from eight class, and make it sample as much ie class XI IPS 1 had 38 participants educate. On every cycle held 2 meetings with 4 stages arranged ie planning, implementation action, observation, and reflection. From the results analysis and calculation of the data obtained that's it on stage before action / pre-action obtained mark complete classic low namely 45%. On learning through implementation approach constructivism has increase motivation learn history as seen from mark results Study students in the main discussion incident Proclamation Indonesian Independence in class XI at SMAN 2 Medan. This matter indicated by activity student in the learning process by researchers in cycle I, meeting 1 and meeting 2, was 60% and 63.3% and increased in cycle II, meeting 1 and meeting 2, namely amounting to 80.1% and 94.8% were in very good category. As well as teacher activities in the learning process experience increase, namely in cycle 1 amounted to 62.5% and 68.2% and increased in cycle II amounted to 80.7% and 94.3%. Improvement results Study can seen in cycle I, meeting 1 and meeting 2, completeness classical 45% and 55% with amount completed students individual. In cycle II, students complete 38 individuals each at meeting 1 and 38 people at meeting 2, with completeness classic 87% and 100%.